Kemampuan Menulis Teks Recount Bahasa Inggris Menggunakan Mind Mapping - Karina, A. Gina Alfiyah (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. The purpose of this research is to determine the improvement of students' ability in writing English recount texts using mind mapping. The researcher applied classroom action research (CAR). The sample of this research was 7th-grade students at SMP Negeri 17 Makassar. The instrument used to collect data was the implementation of 2 cycles: planning, acting, observing, and reflecting. The results of this research indicate an increase in students' scores from the diagnostic test to cycle I and cycle II. In the diagnostic test, only 5 students achieved scores >75. In the second test (cycle I), only 15 students (40%) out of 36 students scored >75. In the second test (cycle II), 33 students (90%) out of 36 students scored >75. It can be concluded that the use of mind mapping can improve students' ability in writing English recount texts in the 7th-grade at SMP Negeri 17 Makassar. Keywords: Recount text, Mind Mapping, Writing Skills